PENGARUH PEMBERIAN KULIT BUAH KAKAO FERMENTASI DENGAN TIGA JAMUR BERBEDA TERHADAP KONSUMSI BAHAN KERING DAN KECERNAAN NUTRIEN PAKAN PADA KAMBING JANTAN - Syahrir, Syahrir (AgriSains, 2011)
The objective of this experiment was to determine effects of cocoa pod fermented with three different types of fungi on dry matter intake and nutrients digestibilities in male goat. This experiment was conducted at experimental house of Animal Husbandry Department, Faculty of Agriculture, Tadulako University between 1st January and 31st Maret 2010. A completely randomized block design with three experimental treatments and five replications was applied in this study. Results of variance analysis showed that fermentation of cocoa pod with three different types of fungi exhibited a highly significant effect (P<0.01) on the animals dry matter intake and total tract digestibilities of feed crude protein, crude fibre, nitrogen-free extracts, neutral detergent fibre, and hemicellulose. Cellulose digestibility, on the other hand, was not significantly affected by treatment (P>0.05). Animals fed with cocoa pod fermented with Aspergillus niger showed the highest feed intake dry matter, and total tract digestibility of feed crude fiber, nitrogen-free extracts, neutral detergent fibre, while the highest crude protein digestibility was found for cocoa pod fermented with Saccharomices sereviseae. In conclusion, fermentation of cocoa pod with fungi used in the present study increased feed digestibility, and hence it is recommended to use Aspergillus niger for fermenting the cocoa pod for use as an animal feed. Key words: Cacao pod, fermentation, nutrient digestibilities.